A Spatial Analysis of Child Labour Utilization in the Tourism Industry of the Eastern Tourism Region of Sri Lanka: Issues and Challenges - Han, Hettiarachchi; TMSPK, Thennakoon (European Scientific Journal, ESJ, 2019)
Tourism is the world’s leading and fastest growing industry which generates many positive impacts on the destinations. It is also considered as a root cause of generating different socio-cultural problems. Employing of child labor in different tourism related activities is a prominent issue and it has now become a common jeopardy and a public debate, especially among social scientists. Therefore, an incessant attention has been given to study the different facets of this issue. This background is common in the Sri Lankan tourism industry too. The main objective of this research was to study the issues and challenges of utilizing child labor in the tourism industry of the Eastern Tourism Region of Sri Lanka. After a preliminary survey, Ampara, Trincomalee and Batticaloa districts were selected as the study area. The judgment and purposive sampling methods were used to select the sample and the total sample of this research was 190, which comprised of 140 child workers and 50 tourism related establishments. Both quantitative and qualitative methods were employed to collect data. The data was analyzed applying qualitative and quantitative analytical methods. The overall findings of the study are discussed under several sub headings including the overall nature of the child labour utilization with main facets such as the existing nature and types of work, the place of work, salaries and wages, different problems faced by child workers and the existing issues and challenges. As per the general findings of the research the child workers of the study area have been employed in both formal and informal sectors of the tourism industry. The issues related to child labour utilization are in two main forms viz. the different issues and challenges faced by child labourers and the business community of the study area.